BIOMASS AND CHLOROPHYLL ANALYSIS OF Ceriops tagal IN DIFFERENT NURSERY MEDIA - Jannah, Herna Maghfira Raudhatul; Ardli, Erwin Riyanto; Proklamasiningsih, Elly (Fakultas Biologi Universitas Jenderal Soedirman, 2021)
Ceriops tagal is a major mangrove species that contributes significantly to the mangrove environment. Ceriops tagal is a species of mangrove that supports a variety of marine organisms, including fish, shrimp, nematodes, and other biota, as well as maintaining the mangrove ecosystem's stability. A nursery is required in the recovery process. The addition of husk and husk charcoal to nursery media can enhance water, air, and plant nutrient absorption space. The objective of this study is to (1) determine how different nursery media with a mixture of husk and husk charcoal affect mud media, and (2) find which nursery media has the best influence on biomass and chlorophyll content in C. tagal mangroves. This study began with the propagules of C. tagal being planted in different composition growing media with husk and husk charcoal, and then calculating the biomass in the root, stem, leaves, and hypocotyl, as well as the chlorophyll content in the leaves of C. tagal organs, using an ANOVA test. Then, for the wet biomass of the root, dry biomass of the stem, root, and wet and dry biomass hypocotyl of C. tagal, do an honest significant difference test of 5%. According to the findings, adding husk and husk charcoal to nursery media can increase the dry biomass of the root and stem, as well as the wet and dry biomass of the hypocotyl in C. tagal organs. Media 5 (mud + husk charcoal in a 2:1 ratio) and media 6 (mud + husk + husk charcoal in a 1:1:1) were the best media for increasing the biomass of the C. tagal in each organ. Environmental factors such as the pH content of the medium influence the increase in dry biomass of the root and stem, as well as the wet and dry biomass of the hypocotyl. Keywords: biomass, Ceriops tagal, chlorophyll, nursery media